The Relationship Between Screen Time on Daily Devices and Emotional Intelligence Capabilities on Adolescents - Zaki Ghiffari, Syahgita; Yenny, Yenny (International Journal of Educational Research & Social Sciences, 2026)
Emotional intelligence (EI) is an essential skill to have during adolescence. The increasing use of digital devices in daily life may affect adolescents’ emotional development through prolonged screen time. The purpose of this study was to find the relationship between screen time on daily devices and emotional intelligence abilities in adolescents. This cross-sectional study was conducted between October and December 2025 at a Private Senior High School. A total of 90 respondents were selected using a consecutive non-random sampling method. Data collected included age, gender, daily device use, and family factors such as family gatherings, family attendance, and parents highest education level, as well as screen time and EI. EI was determined by the Trait Emotional Intelligence Questionnaire – Short Form (TEIQue-SF). Fisher's exact test was used in data analysis. The results showed that 76 (84.4%) respondents were aged ≥ 17 years, while 47 (52.2%) were female, most of the respondents 80 (88.9%) chose smartphones as their frequently used daily devices, most or 50 (55.6%) respondents gathered ≥ 5 times per week with family, almost all 86 (95.6%) respondents revealed family attendance at important events, and as many as 48 (53.3%) of the respondents' parents had a bachelor's/bachelor's degree, 78 (86.7%) respondents used their daily devices for > 2 hours, and the respondents' EI level was dominated by the high category, namely 73 (81.1%). Significant relationship was found between screen time on daily devices and EI in adolescents (p = 0.046). Family interventions related to adolescents screen time should be strenghten.